Detection of Hepatits C Virus (HCV) by ELISA, RIBA and Reverse Transcriptase- Polymerase Chain Reaction (RT-PCR) Technique among Kidney dialysis patients in Nineveh Governorate/Iraq. - Basima A. Abdullah (University of Thi-Qar Journal of Science, 2019)
Introduction: the silent disease (Hepatitis C virus) is considered as one of the major causes of chronichepatitis and cirrhosis, hence the aims of study to detect Hepatitis C virus among hemodialysis and peritonealdialysis in Nineveh Governorate/Iraq.Patients and Methods: (80) blood samples were collected from dialysis patients 46 (57.5%) males, (42.5%)females at age (15-60) years, the average age (37.5) years, include (50) heamodialysis patients, (30)peritoneal patients and (100) person from health blood donors as a control group.We used ELISA version 3.0 to detect anti-HCV and confirm the positive and equivocal results byRecombinant Immunoblot Assay version 3.0 (RIBA HCV 3.0), and used Reverse Transcribtase PolymeraseChain reaction (RT-PCR) to confirm positive and equivocal results by RIBA technique.Results: the current study showed significant differences (P≤0.05) between percentage of ant i-HCV andHCV RNA between heamodialysis, peritoneal dialysis and control group. The percentage of anti-HCV whentested by ELISA in serum of heamodialysis patients was (48%) positive, (48%) negative, (4%) equivocal,while (2%) positive (98%) in serum of peritoneal dialysis, (1%) positive, (99%) negative in control group.We used RIBA technique to confirm positive and equivocal results in ELISA the results showed (44%) positive, (52%) negative and (4%) equivocal between heamodialysis patients, (2%) positive, (98%) negativebetween peritoneal dialysis, while showed (1%) positive, (99%) between control group.We used (RT-PCR) to confirm positive and equivocal results in RIBA technique; it showed (50%) positivebetween heamodialysis patients, (2%) positive in peritoneal dialysis, (1%) positive in control group.Conclusion: the prevalence of Hepatitis C virus was higher in Heamodialysis than peritoneal dialysis inNineveh Governorate/Iraq.